Practice Teachersâ Possible Solutions to Studentsâ Problems of Speaking during PPL in Junior High Schools - Isworo, Chezia Eufresia (LLT Journal: A Journal on Language and Language Teaching, 2016)
Program Pengalaman Lapangan (PPL) or School-based Practicum is one of the compulsory courses that must be taken by all English Language Education Study Program (ELESP) Sanata Dharma University students. PPL requires the students, who are called practice teachers, to do teachersâ job at school. As English practiceÂ teachers, there is a possibility that they might face a lot of problems related to theÂ condition and situation in the school, either from the studentsâ side, teachersâ side,Â or other factors. This research focuses on junior high school studentsâ problems of speaking and the possible solutions to the problems based on the ELESP studentsâ experiences as English practice teachers. From the findings, it is expected that future practice teachers and English teachers can anticipate similar problems and apply the possible solutions when they work at schools.Â DOI: https://doi.org/10.24071/llt.2016.190102